Sistem Informasi Penjualan Aksesoris Handphone Pada Toko Mitra Ponsel Berbasis Web - Syahfitri Hrp, Sri Rahmadani (Journal of Computer Science and Information System(JCoInS), 2020)
Mitra Ponsel Store is a store that is engaged in selling mobile phone accessories. The sales process still uses a common way in which customers come directly to the store to make a purchase. By building a web-based sales information system at the Cellphone Partner Store, it can help stores and consumers in buying and selling transactions and promoting products through the internet. Program implementation uses PHP programming language with MYSQL database. The results of this study are in the form of a web-based sales system design that can facilitate sales transactions, expand consumer reach and increase the number of sales at the Mobile Partner Store. Test Results with blackbox.